Methadone—Not a magic bullet in melanoma therapy. Issue 6 (21st June 2018) - Brüggen, Marie‐Charlotte; Mangana, Joanna; Irmisch, Anja; French, Lars E.; Levesque, Mitchell P.; Cheng, Phil F; Dummer, Reinhard
Abstract: Methadone (Met) mainly acts as a μ‐opioid receptor agonist. Recent evidence pointing towards the role of Met in sensitization of certain cancer cell lines to chemotherapeutic agents has promoted the hypothesis that Met may be a useful adjuvant to cancer chemotherapy. We wanted to address whether Met has, alone or in combination with a chemotherapeutic agent, an effect on melanoma cell viability in vitro. Only a small fraction (4.3%) of our 102 melanoma biobank cell lines with RNA‐sequencing data showed expression of the main receptor for Met (OPRM1). We assessed the viability of melanoma cell lines with high, medium or low/no OPRM1 expression (OPRM1 high, OPRM1 med, OPRM1 neg ) 72 hours after treatment with Met alone or combined with cisplatin (Cis). Our analyses show that Met alone did not affect cell viability. While Cis/Met treatment did not have an effect on viability of OPRM1 med or OPRM1 neg cell lines, it resulted in a slightly decreased cell viability of OPRM1 high cells. Clinically, concurrent temozolomide/Met treatment did not have an effect in our single‐case report of a patient suffering from uveal melanoma. Taken together, our findings do not provide evidence for recommending Met as an adjuvant to chemotherapy in patients with melanoma.